Tantangan dan Peluang Pendidikan Agama Kristen bagi Generasi Alpha di Era Teknologi di Kota Batam - SUHARTONO, TONY (JURNAL IMPARTA, 2025)
This study aims to identify the challenges and opportunities in implementing Christian Religious Education (PAK) for Generation Alpha in the technological era, particularly in Batam City a dynamic industrial and port city with complex social structures. Generation Alpha is the first generation to be born into a fully digital environment, resulting in unique characteristics in learning, thinking, and the formation of faith-based values. Using a qualitative approach through a literature study method, this research analyzes various academic sources and relevant materials related to generational development, digital learning theories, and current PAK practices. The findings reveal that the primary challenges of PAK for Generation Alpha include declining spiritual attention, the dominance of instant digital media, and the disparity in teachers’ abilities to adapt to technology. On the other hand, significant opportunities arise in utilizing technology as a means of conveying faith values through creative approaches such as gamification, interactive media, and project-based learning. This study highlights the urgent need to transform PAK methods and curricula to be contextual and relevant to the digital world. Teachers, parents, and Christian educational institutions in Batam must collaborate to develop an interactive and value-driven model of PAK. Future research is recommended to explore the empirical effectiveness of digital media in shaping the faith character of Generation Alpha.